Managing with power politics and influence in organizations - Pfeffer, Jeffrey (Boston Harvard Business School Press, 1992)
Although much as been written about how to make better decisions, a decision by itself changes nothing. The big problem facing managers and their organizations today is one of implementation--how to get things done in a timely and effective way. Problems of implementation are really issues of how to influence behavior, change the course of events, overcome resistance, and get people to do things they would not otherwise do. In a word, power. Managing With Power provides an in-depth look at the role of power and influence in organizations. Pfeffer shows convincingly that its effective use is an essential component of strong leadership. With vivid examples, he makes a compelling case for the necessity of power in mobilizing the political support and resources to get things done in any organization. He provides an intriguing look at the personal attributes?such as flexibility, stamina, and a high tolerance for conflict?and the structural factors?such as control of resources, access to information, and formal authority?that can help managers advance organizational goals and achieve individual success
Keywords: Decision-making; Power (Social sciences); Organizational behavior; Management Leadership